Ultrasonography study: Supraspinatus muscle thickness evaluation on dominant versus non dominant shoulder on tennis players - Papandreou, M.; Billis, E.; Georgoudis, G.; Papathanasiou, G.; Gliatis, J. (Journal of Exercise, Sport & Orthopedics, 2016)
The supraspinatus is the most commonly damaged structure in rotator cuff muscles in overhead sports. Supraspinatus injuries affect its strength causing atrophy and reduce shoulder functionality. Ultrasonography imaging (US) provides information on the supraspinatus morphological features, such as muscle thickness (MT). The ability to perform assessment of supraspinatus MT on dominant and non dominant shoulders on tennis players -as overhead athletes- has not been studied and may be of value in assessment and treatment. The purpose of this cross sectional study was to evaluate the differences in the supraspinatus MT between the dominant and non-dominant shoulder on tennis players using brightness-mode US.